Optimal placement of steel plate shear walls for steel frames by bat algorithm. (17th January 2014) - Gholizadeh, Saeed; Shahrezaei, Amir Masoud
SUMMARY Layout optimization of steel frames with steel plate walls (SPWs) using a meta‐heuristic search algorithm is the main aim of the present study. SPWs are lateral load‐resisting systems, especially against earthquake excitation. These systems offer significant advantages in terms of cost, performance and ease of design compared with other systems. In this study, orthotropic membrane model is used to model the behaviour of steel plate shear walls. The newly developed bat algorithm, which is based on the echolocation behaviour of bats, is employed as the present study optimizer. Design variables of the optimization problem consist of the cross sections of beams and columns of the frame, the web plate thicknesses of SPWs and the placement of SPW in the frame. The bat algorithm performs suitable selection of sections from the AISC wide‐flange (W) shapes list. Strength constraints of the American Institute of Steel Construction Load and Resistance Factor Design and displacement constraints are checked during the optimization process. The results reveal the effectiveness of the proposed method for optimization of steel frames with SPWs. Copyright © 2014 John Wiley & Sons, Ltd.